1997
DOI: 10.1042/bj3260205
|View full text |Cite
|
Sign up to set email alerts
|

Altered regulation of cholesterol and cholesteryl ester synthesis in Chinese-hamster ovary cells overexpressing the oxysterol-binding protein is dependent on the pleckstrin homology domain

Abstract: Oxysterol-binding protein (OSBP) is a high-affinity receptor for a variety of oxysterols, such as 25-hydroxycholesterol, that down-regulate cholesterol synthesis and stimulate cholesterol esterification. To examine a potential role for OSBP in regulating cholesterol metabolism, we stably overexpressed this protein in Chinese-hamster ovary (CHO)-K1 cells. Compared with mock-transfected controls, several cell lines overexpressing wild-type OSBP (CHO-OSBP) displayed a 50% decrease in cholesteryl ester synthesis w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
134
1

Year Published

1999
1999
2010
2010

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 113 publications
(139 citation statements)
references
References 39 publications
4
134
1
Order By: Relevance
“…This result indicates that the effect of OS on the sphingomyelin and cholesterol concentration may be cell-specific. In MCF-7 cells, OS appears to elevate phospholipids and cholesterol with less specificity for sphingomyelin than reported for other cell types (42)(43)(44)(45). The effect of OS on cholesterol was verified by filipin staining of OS-incubated MCF-7 cells, which showed accumulation of cholesterol in lamellipodia or at the membranes of adjacent cells (not shown).…”
Section: Discussionmentioning
confidence: 72%
See 1 more Smart Citation
“…This result indicates that the effect of OS on the sphingomyelin and cholesterol concentration may be cell-specific. In MCF-7 cells, OS appears to elevate phospholipids and cholesterol with less specificity for sphingomyelin than reported for other cell types (42)(43)(44)(45). The effect of OS on cholesterol was verified by filipin staining of OS-incubated MCF-7 cells, which showed accumulation of cholesterol in lamellipodia or at the membranes of adjacent cells (not shown).…”
Section: Discussionmentioning
confidence: 72%
“…Binding of OS to ORPs has been shown to participate in the Golgi translocation/anchoring and activation of ORPs (42)(43)(44)(45). It has also been found that an activated, Golgi-localized OS-ORP complex modulates the biosynthesis or transport of sphingomyelin and cholesterol (16 -21, 42-45).…”
Section: Discussionmentioning
confidence: 99%
“…The cytosolic oxysterol-binding protein OSBP was identified in the 1980s (Taylor et al, 1984;Taylor and Kandutsch, 1985), and a role for the protein in cholesterol and sphingomyelin metabolism has been implicated previously (Lagace et al, 1997(Lagace et al, , 1999. Families of proteins homologous to OSBP have recently been identified in eukaryotic organisms from yeast to human .…”
Section: Introductionmentioning
confidence: 99%
“…Lagace et al 14 showed that OSBP overexpression in CHO cells results in a 40-60% decrease in acyl-CoA: cholesterol acyltransferase activity and its mRNA, a 50% elevation in the mRNA levels of several sterol regulated genes (LDL receptor, HMG-CoA reductase and HMG-CoA synthase), and an 80% elevation in cholesterol biosynthesis. The observed changes in mRNA levels suggest that OSBP affects transcriptional control of the sterol homeostatic machinery.…”
Section: -3)mentioning
confidence: 99%